2016
DOI: 10.1016/j.molcel.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Architecture Organized by Rif1 Underpins the Replication-Timing Program

Abstract: Summary DNA replication is temporally and spatially organized in all eukaryotes, yet the molecular control and biological function of the replication-timing program are poorly understood. A role for three-dimensional chromatin organization has been proposed. Rif1 is required for normal genome-wide regulation of replication timing, but its molecular function is poorly understood. Here we show that in mouse embryonic stem cells Rif1 coats late replicating domains and, together with Lamin B1 identifies the majori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
261
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(299 citation statements)
references
References 69 publications
31
261
2
Order By: Relevance
“…Genome-wide analyses of Rif1 in mouse embryonic stem (ES) cells showed that Rif1 binds to large domains which coincide with the late-replicating domain and lamin B1-assoicated domain (Foti et al, 2016). This is consistent with the result from fission yeast, supporting the notion that chromatin-bound Rif1 suppresses origin firing.…”
Section: Recruitment Of Phosphatase By Rif1supporting
confidence: 65%
See 2 more Smart Citations
“…Genome-wide analyses of Rif1 in mouse embryonic stem (ES) cells showed that Rif1 binds to large domains which coincide with the late-replicating domain and lamin B1-assoicated domain (Foti et al, 2016). This is consistent with the result from fission yeast, supporting the notion that chromatin-bound Rif1 suppresses origin firing.…”
Section: Recruitment Of Phosphatase By Rif1supporting
confidence: 65%
“…In the absence of Rif1, chromatin loops are lost and chromatin is decondensed and becomes more dynamic (Masai et al, unpublished data). The 4C-Seq assays indicated that chromatin interactions between different timing domains increase in the absence of Rif1 (Foti et al, 2016), reflecting a more mobile nature of the chromosomes. Red and blue lines indicate, respectively, mid-S/ late-and early-replicating chromosome segments.…”
Section: Recruitment Of Phosphatase By Rif1mentioning
confidence: 98%
See 1 more Smart Citation
“…Our data are consistent with the idea that loss of the phosphatase causes premature Mcm4 hyper-phosphorylation, thus causing promiscuous activation of replication origins and disruption of the timing program (Figure 7D, top). This function of Rif1 can occur concomitantly with its proposed role in organizing 3D chromatin structure, which was recently shown to affect replication timing and 3D nuclear organization in mouse cells (Foti et al., 2016). This altered 3D chromatin structure may cause improper regulation of MCM phosphorylation.…”
Section: Discussionmentioning
confidence: 93%
“…Depletion of Rif1 results in a consolidation of early-and late-replicating domains to be instead replicated in mid-S phase (or randomly throughout S phase) (Cornacchia et al 2012). Rif1 localizes to late-replicating domains, many of which are concordant with LADs (Foti et al 2016). Late-replicating regions of the genome marked only by Rif1 are most susceptible to advancing their time of replication in the absence of Rif1 function.…”
Section: Regulation Of Origins On the Chromosome Scalementioning
confidence: 99%